Aortic cusp abnormalities in patients with trileaflet aortic valve and root aneurysm. Issue 1 (8th July 2022) - Ehrlich, Tristan; Hagendorff, Andreas; Abeln, Karen; Froede, Lennart; Giebels, Christian; Schäfers, Hans-Joachim
Abstract : Background: The frequency of concomitant cusp pathology in aortic root aneurysm with or without aortic regurgitation is not well known, and the sensitivity and specificity of two-dimensional trans-oesophageal echocardiography (2D TEE) in its detection has not yet been specified. Objectives: We analysed the type and frequency of concomitant cusp alterations in root aneurysm referred for surgery. Sensitivity and specificity of 2D TEE in detecting these alterations were determined. Methods: In 582 patients (age 56.8±15.4 years, 453 male) with trileaflet aortic valves undergoing root replacement for regurgitation (n=347) or aneurysm (n=235), details of valve morphology were analysed. In a subcohort (n=281), intraoperative TEEs were analysed retrospectively and correlated with the intraoperative findings. Results: Any cusp pathology was present in 90.9% (prolapse: n=473; retraction: n=30; calcification: n=14; fenestration: n=12), morphologically normal cusps were seen in only 52 patients (8.93%). Valve-sparing surgery was performed in 525 (90.2%) instances, composite replacement in 57 (9.8%). Preoperative TEE correctly identified any postroot repair prolapse in 70.6% and any retraction in 85%. The sensitivity of TEE in detecting any prolapse was 68.6% (specificity of 79.5%). The sensitivity was highest for the right cusp and intermediate for the non-coronary. Conclusions: Cusp prolapse is frequent in root aneurysm and trileaflet aortic valves. Prolapse is underdiagnosed by 2D TEE in many cases because pre-existent stretching of cusp tissue is masked by the geometric effects of root dilatation.